Effect of Betty Neuman's systemic model on the anxiety of patients undergoing endoscopy: A randomized control trial - Reza Mirafzali; Maryam Laeli; Fatmeh Ghanbari; Negarin Akbari (Journal of Nursing Advances in Clinical Sciences)
The present study aims to determine the effect of Betty Neuman's systemic model on the anxiety of patients undergoing endoscopy. This randomized control trial investigation involved 44 participants recruited from the endoscopy center of Golestan Province Hospital in the 2022, specifically those prescribed for endoscopic procedures. The data collection instruments employed in this research encompassed a demographic characteristics questionnaire focusing on age, gender, education, and occupation, as well as Spielberger's state-trait anxiety questionnaire (form Y) (STAI-Y). The pre-intervention anxiety levels were 111.41 (SD=17.61) in the intervention group and 109.27 (SD=6.64) in the control group. The Mann-Whitney U test indicated no statistically significant difference in the anxiety levels between the two groups before the intervention (P=0.29). Following the intervention, the anxiety levels were 116.56 (SD=12.25) in the intervention group and 111.95 (SD=4.70) in the control group. The independent t-test revealed a significant difference between the two groups (P<0.01). Furthermore, the Wilcoxon test demonstrated no significant difference in anxiety levels within the control group before and after the intervention (P=0.36), whereas a significant difference was observed in the intervention group before and after the intervention (P<0.01). Moreover, the ANCOVA revealed a statistically significant difference between the two groups after accounting for the pre-test effects (Eta=0.58, P<0.01). This indicates that 58% of the variance in post-test changes can be attributed to the training provided based on the Betty Neuman's systemic model. In conclusion, the implementation of Betty Neuman's systemic model has proven to be effective in reducing anxiety levels among patients undergoing endoscopy. The demonstrated efficacy of Betty Neuman's model suggests that nursing models can serve as a cost-efficient, impactful, and secure treatment approach in patient care.